CARCASS AND ORGANS CHARACTERISTICS OF BROILER CHICKENS FED DIETARY LEVELS OF SICKLE POD (CASSIA TORA) SEED AND SUNFLOWER SEED MEALS - Musa, A.; Abubakar, M. M.; Muhammad, A. S.; Mancha, Y. P. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
An experiment was conducted to evaluate carcass and organs characteristics of broiler chicken fed dietary levels of sickle pod (Cassia tora) seed and sunflower seed meals. It was carried out at the poultry unit of Teaching and Research Farm, Federal College of Horticulture (FCH) Dadin kowa, Gombe State, Nigeria to evaluate carcass and organs characteristics of broiler chickens using sickle pod seed (Cassia tora) and sunflower seed meals based diets. Five experimental diets each for both starter (23% CP) and finisher (20% CP) were formulated in which Cassia tora meal replaced sunflower meal at 0, 20, 30, 40 and 50% designated as diets A, B, C, D and E respectively. Three hundred (300) day old broiler chicks were randomly allocated to the five diets in four replicates of fifteen birds each. The experimental feeds and water were supplied to the birds ad libtum and the feeding trial lasted for seven weeks. The results indicated that live (1.16-1.49kg) and carcass (0.81-1.10kg) weight as well as dressing percentage (68.56-73.87%) were significantly (P<0.001) influenced by the Cassia tora diets. Eviscerated weights (1.07-1.30kg) were not significantly affected by the dietary treatments. However, most organ parameters were not significantly affected except small and large intestine lengths with values of 169.25-216.67cm and 8.00-14,00cm respectively as well as gizzards (2.79-3.67%) at P<0.001. It was concluded that Cassia tora seed meal can be included into broiler chicken diets when properly processed. It can replace up to 50% sunflower seed meal in broiler chicken diets without affecting the carcass yield and other organs characteristics. It was recommended that 50% toasted Cassia tora seed meal can be used in broiler chicken diets to improve carcass yield.